A faunistic study on laelapid mites in Urmia, Iran - Mohammadreza Kavianpour; Younes Karimpour; Alireza Nemati; Shahram Mirfakhraei (Iranian Journal of Animal Biosystematics, 2017)
Based on this survey 23 species of family Laelapidae have been identified which three species of them are reported as new for Iranian mites fauna, that are marked with asterisk. The list of identified genera and species is as follows: Laelapidae: Gaeolaelaps aculeifer (Canestrini, 1884); G. oreithyiae (Walter and Oliver, 1989); G. angustus (Karg, 1965); G. kargi (Costa, 1968); G. nolli (Karg, 1962); G. khajooii Kazemi, Rajaei and Beaulieu, 2014; Pneumolaelaps (Hypoaspisella) linteyini (Samsinak, 1964); P. (H.) berlesei* (Hirschmann, 1969);Cosmolaelaps vacua (Michael, 1891); C. lutegiensis (Shcherbak, 1971); C. malakutsilus* Rosario, 1981; C. ornatus (Berlese,1903); C. angustiscutatus (Willmann, 1951); Laelaspis astronomicus (C. L. Koch, 1839); L. equitans (Michael, 1891); Ololaelaps sellnicki* Bregetova and Koroleva, 1964; Euandrolaelaps karawaiewi (Berlese, 1903); Hypoaspis larvicolus Joharchi and Halliday, 2011; Pogonolaelaps canestrinii (Berlese, 1903); Gymnolaelaps artavilensis Joharchi and Halliday, 2013; Pseudoparasitus dentatus (Halbert, 1920); Androlaelaps casalis (Berlese, 1887); A. shealsi (Costa, 1968)